Experimental wavelet transient-state analysis of electrical machines directly feeding by photovoltaic cells - (:unkn) unknown (My University, 2009)
Solar electric systems -also known as photovoltaic (PV) systems- have very little impact on the environment, making them one of the cleanest power-generating technologies available. While they're operating, PV systems produce no air pollution, hazardous waste, or noise, and they require no transportable fuels. In PV System design, the selection and proper installation of appropriately-sized components directly affect system reliability, lifetime, and initial cost. The features of the receivers fed from PV systems have a direct impact on the cells; namely, the power generators of the system. System behavior may change in receivers equipped with electrical machines fed from photovoltaic's, depending on the characteristics of the machine used. The fact that in the design phase of the photovoltaic systems which will feed electrical machines that the current drawn by any electrical machines at the startup is higher than the nominal operating current should be taken into account. In this study, the startup and nominal operating behaviors of electrical machines directly connected to photovoltaic system (not having any storage system or controller system) were empirically examined, obtained power values (in p.u.) were decomposed to sub-frequency components by means of the discrete wavelet transform than they were compared to each others.
Keywords: Electrical machines; Multiresolution analysis; Photovoltaic cells; Transient state; Wavelet filter bank